Pembentukan Peradilan Agama Hindu di Indonesia: Landasan Filosofis, Yuridis, dan Sosiologis - Hadriani, Ni Luh Gede; Gelgel, I Putu; Wibawa, Putu Sastra (Jayapangus Press, 2025)
Hindus really need Religious Courts, because so far the District Courts have not been able to handle legal issues for Hindus, especially issues related to family law such as divorce, marriage and inheritance law. So far the formation of religious courts for Hindus has not been recognized because it does not have a clear basis. Therefore, it is necessary to conduct research on the basis for the formation of religious courts for Hindus, both the legal, philosophical and sociological basis of the formation of Hindu Religious Courts in Indonesia. The purpose of this study is to analyze the basis for the establishment of Hindu Religious Courts in Indonesia. The approach used is legal-sociological. This study found the basis for Religious Courts, namely philosophical, legal and sociological foundations. By finding the basis for the formation of Religious Courts for Hindus, it is hoped that Religious Courts for Hindus can be realized